2020
DOI: 10.33073/pjm-2020-023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorella vulgaris on Growth and Photosynthetic Pigment Content in Swiss Chard (Beta vulgaris L. subsp. cicla)

Abstract: Microalgae application in agriculture is an alternative measure that could be highly beneficial to plants. The application of microalgae Chlorella vulgaris S45 and its effect on plant growth and pigment content in Swiss chard were investigated. In the treatments, 5% and 10% algal suspensions were applied by spraying on plants and in soil, respectively. C. vulgaris S45 affected the initial growth of Swiss chard and the content of photosynthetic pigments positively. The correlation analysis proved the existence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Indeed, this ratio being used as an indicator of N partitioning in leaves, it seems to be positively correlated with the ratio of PSII cores, supporting higher light captures by the chlorophyll-protein complex [39]. In accordance with previous results, Hajnal-Jafari et al [21] found that treatments with 5% and 10% C. vulgaris suspensions applied on soil and Swiss card, respectively, positively affected the content of photosynthetic pigments, showing a correlation analysis between chlorophyll a content and leaf number, and chlorophyll b content and fresh leaf weight. Total protein contents extracted from the shoots and roots of lettuce seedlings are reported in Table 4.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, this ratio being used as an indicator of N partitioning in leaves, it seems to be positively correlated with the ratio of PSII cores, supporting higher light captures by the chlorophyll-protein complex [39]. In accordance with previous results, Hajnal-Jafari et al [21] found that treatments with 5% and 10% C. vulgaris suspensions applied on soil and Swiss card, respectively, positively affected the content of photosynthetic pigments, showing a correlation analysis between chlorophyll a content and leaf number, and chlorophyll b content and fresh leaf weight. Total protein contents extracted from the shoots and roots of lettuce seedlings are reported in Table 4.…”
Section: Resultssupporting
confidence: 91%
“…Indeed, foliar spray application of microalgae-based products was recently considered as a promising and innovative agricultural technique, as it is safe to the environment, increases agricultural sustainability, and achieves high yield in crop production [11,19,20]. The application of 5% and 10% microalgal suspensions of C. vulgaris by spraying plants of Swiss chard and in soil, respectively, positively affected the initial growth of Swiss chard, and the content of photosynthetic pigments [21].…”
Section: Introductionmentioning
confidence: 99%
“…C. vulgaris microalgae is an efficient, economical and safe biofertilizer to substitute for chemical fertilizers in enhancing plant growth (Agwa et al, 2017). When it comes to C. vulgaris, the results obtained by Hajnal-Jafari et al (2020b) related to the growth and development of Swiss chard were in accordance with our data. In order to assess the effects of C. vulgaris on agronomic and physiological responses, the authors studied the growth parameters in Swiss chard plants using C. vulgaris as a biofertilizer.…”
Section: ____________________________________________________________ ___________________________________________________________________supporting
confidence: 87%
“…The presence of C. vulgaris in the cultivation medium of Lactuca sativa promoted its growth and significantly increased fresh and dry weight of seedling, as well as pigment content [36]. Similar effects of this microalgae have been shown on sugar beet and tomato plants [37][38][39][40]. Some authors have suggested that the stimulation of pigment biosynthesis and the increased pigment content may improve photosynthetic activity [40], but there is no direct evidence.…”
Section: Introductionmentioning
confidence: 95%